1996
DOI: 10.1007/bf03160686
|View full text |Cite
|
Sign up to set email alerts
|

Beaver ponds create wetland habitat for birds in mountains of southeastern Wyoming

Abstract: We studied the use of beaver ponds and associated wetlands by ducks and waterbirds on the Laramie Range, Albany County, Wyoming, during 1994. Our goal was to identify physical habitat features of beaver ponds associated with use by migrating, breeding, and postbreeding ducks and other birds associated with aquatic habitats. Species richness of birds observed at beaver ponds was positively correlated with water surface area, area of shallow water, length of woody shoreline, and shoreline development (the ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…In other forested regions of North America, beaver ponds have been recognized as important waterfowl breeding habitats, because they are used by all dabbling ducks, wood duck, hooded merganser, and ring-necked duck (Renouf 1972;Brown and Parsons 1979;Brown et al 1996;McCall et al 1996;Rempel et al 1997;Longcore et al 2006). This species assemblage would fit our results perfectly if we rely on flooded swamps as indicators of beaver ponds.…”
Section: ŝ > 1)supporting
confidence: 81%
“…In other forested regions of North America, beaver ponds have been recognized as important waterfowl breeding habitats, because they are used by all dabbling ducks, wood duck, hooded merganser, and ring-necked duck (Renouf 1972;Brown and Parsons 1979;Brown et al 1996;McCall et al 1996;Rempel et al 1997;Longcore et al 2006). This species assemblage would fit our results perfectly if we rely on flooded swamps as indicators of beaver ponds.…”
Section: ŝ > 1)supporting
confidence: 81%
“…The transition from aquatic to terrestrial areas may be characterised by flooded emergent vegetation (Grover & Baldassarre , Brown et al. , Ray et al. ), a grass–forb–shrub layer next to ponds (Edwards & Otis , Martell et al.…”
Section: Review Of the Impacts Of Beavers On Biodiversitymentioning
confidence: 99%
“…Following reintroduction of beaver to the San Pedro River (see ‘History and status’ above), Johnson () found that abundance and species richness of obligate riparian birds were correlated with presence and age of beaver dams even after controlling for covariates such as presence of surface water and density of riparian vegetation. Waterfowl presence in dryland streams is also strongly associated with beaver ponds (Brown et al ., ; McKinstry et al ., ). Collectively these studies indicate strong and positive relationships between presence of dryland beaver ponds and the overall abundance and species richness of riparian‐associated bird communities.…”
Section: Biotic Effectsmentioning
confidence: 99%